2022
DOI: 10.31219/osf.io/y3s69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are larger cities more central in urban networks: A meta-analysis

Abstract: As cities develop more and longer-range external relations, some have challenged the long-standing notion that population size indicates a city's power in its urban system. Instead, they contend that cities' centrality within urban networks provides a better indicator of power. But are city population size and city network centrality really independent properties in practice, or do larger cities tend to be more central in urban networks? To answer this question, we conducted a systematic literature search and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In the context of urban planning research, centrality measurements have revealed differences between planned and self-organised city structures (Crucitti et al, 2006). Several studies have evaluated the correlation of centrality to land use, density, and population size (Porta et al, 2009; Li and Neal, 2022; Wang et al, 2011). These results suggest that centrality represents urban formation and constitution and is a good way to determine the advantageous location of land and its use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of urban planning research, centrality measurements have revealed differences between planned and self-organised city structures (Crucitti et al, 2006). Several studies have evaluated the correlation of centrality to land use, density, and population size (Porta et al, 2009; Li and Neal, 2022; Wang et al, 2011). These results suggest that centrality represents urban formation and constitution and is a good way to determine the advantageous location of land and its use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urban network studies highlight overlapping hierarchies that vary depending on the type of relationships involved, and often aim to understand the processes that generate particular network configurations among cities. A key task is to identify the most central nodes that dominate the flow of content within the network (Li and Neal, 2022). The centrality of such nodes can be measured in several ways, each highlighting different qualities: Degree counts the number of connections with other cities; Closeness measures the proximity to other cities; Betweenness evaluates the amount of times in which cities operate as links to other cities; and Authority assesses the connections to other important nodes.…”
Section: Inter-referencing Cities: From Mental Maps To Urban Referenc...mentioning
confidence: 99%